Quantificação de cianobactérias produtoras de microcistina no reservatório de Furnas (MG), através da PCR em tempo real, e sua relação com fatores ambientais - Juliana da Silva Martins Pimentel (2009)
Cyanobacteria are photosynthetic prokaryotes found in different aquatic environments. A serious problem in eutrophic waters is the frequent occurrence of blooms of potential toxic cyanobacteria. Since species are sometimes difficult to identify and morphological features are not enough to separate toxic from non-toxic strains, molecular markers have beendeveloped as an instrument to detect toxicity. Microcystin-producing cyanobacteria have a polycistronic operon called mcy that has been used as a genetic tool for toxicity detection. In the present work, samples were collected between September 2006 and April 2008 at several stations in Furnas Reservoir (MG), a large reservoir in Southeastern Brazil. This reservoir is formed by two main rivers, Grande and Sapucaí, and a series of small tributaries. New primers were designed for the conventional PCR and for the quantitative PCR techniques, aiming the detection of mcyD genes in natural populations. Physical-chemical, biological andmolecular analyses were performed on the same sample to study the relationship among the existence of toxic strains and of the environmental factors. The Grande and Sapucaí branches showed different trophic levels. In the Sapucaí, which is more eutrophic, a large number ofcyanobacteria was frequently observed. Some tendency of sazonality was detected in the entire reservoir. It was possible to find some relationship between chlorophyll a, phosphorus and ZE and the amount of toxic genotypes in the environment. The presence of mcyD genes was also positively correlated with the presence of microcystin, but directly quantitative relationships between these two items were not always found. The methodology used for microcystin quantification and identification was very sensitive and it could be used in cyanobacteria monitoring programs. However, more studies are necessary to investigate the influence of environmental factors on the amount of microcystin-producing cyanobacteria in the environment.